(3NQjOI GdbUQ hLQjOI Cgd GdYUQs - (3GdCUagGfj, CHh YHO Gddg, YeGO GdOjf GdcGJH, eMeO Hf eMeO Uaj GdOjf GHf fajS GdOjf MGeO, J(B597(3g`s
(3ChdgG (B:s
(3aEf CeOM EeGeG hgeGe adG CQRe hdG ahGdG , hGfXQ Mjf CaNQ QGFYGJ Jchf dPj MSH efGdG , hGYjJ HGdfSje hdSJ CZTi GdMQGe ajbWQ GdSMQ GdMdGdGs
(3BNQgG (B:s
(3aEfg dG jYhd EdG Ydi eG TjO hHfi hbO ef GdeSGYj GdJj fGdhef jbJQa MSfI fRO dg ajgG MSfis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 7 / 26s
(3eYLe GdeDdajf(B: 3 / 634s
(3cTa GdXfhf(B: 1 / 701s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdCOHs